Perancangan Sistem Customer Relationship Management Terhadap Pengaduan Nasabah Berbasis Web Menggunakan Model Extreme Programming - Adelia Martika; Deanna Durbin Hutagalung (OKTAL : Jurnal Ilmu Komputer dan Sains, 2024)
Bank Capital Indonesia or better known as Bank Capital is a bank that was established in 1989 and has its head office in Jakarta. Companies need to pay attention to the quality of service that can provide an incentive to customers to establish a strong relationship with the company. So far, customers have to come to the office to report complaints. For telephone complaints, errors and omissions often occur in handling, which can slow down the performance of officers in providing services. To overcome this problem, especially regarding the submission of customer complaints to Bank Capital Indonesia, a system is needed that can make it easier for customers, namely the E-CRM system. This system planning model uses the Extreme Programming method. While the data collection methods used are observation, interviews, and literature studies. Then the database used is PHP and MySQL. The results of the study found that this system can design an effective and efficient system in the process of handling customer complaints with a questionnaire assessment result of 93%. With this web-based CRM system, you can design a system that provides fast service and the response is not long so that it doesn't make customers feel bored with the results of the questionnaire assessment, which is 86%. And can design a system that can process and make reports based on customer complaints with the results of the questionnaire assessment being 89%.